2018
DOI: 10.1111/jerd.12432
|View full text |Cite
|
Sign up to set email alerts
|

The One step‐No prep technique: A straightforward and minimally invasive approach for full‐mouth rehabilitation of worn dentition using polymer‐infiltrated ceramic network (PICN) CAD‐CAM prostheses

Abstract: Objectives To introduce a novel approach for full‐mouth rehabilitation of severely worn dentition using polymer‐infiltrated ceramic network (PICN) computer‐aided‐design and manufacturing (CAD‐CAM) restorations, without tooth tissue preparation and provisional phase. Clinical considerations Three patients with generalized tooth wear, suffering from dental pain, masticatory dysfunction, bruxism and neck and back pain, were selected and treated in collaboration with physiotherapists. Occlusal analyses were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…From a functional point of view, the one‐step and empirical VDO increase did not result in any complications. These results confirm previous findings of the one step‐no prep technique for generalized tooth wear, in which PICN restorations are bonded on all teeth, without testing the VDO with provisional restorations 7,29 . The VDO determination is always an inaccurate and empirical process 30 ; generally, it is based on dental restorative needs, and with the one step‐no prep approach, the principle is simply to recreate missing tissues based on the remaining tooth anatomy, since PICN materials can be used in low thickness.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…From a functional point of view, the one‐step and empirical VDO increase did not result in any complications. These results confirm previous findings of the one step‐no prep technique for generalized tooth wear, in which PICN restorations are bonded on all teeth, without testing the VDO with provisional restorations 7,29 . The VDO determination is always an inaccurate and empirical process 30 ; generally, it is based on dental restorative needs, and with the one step‐no prep approach, the principle is simply to recreate missing tissues based on the remaining tooth anatomy, since PICN materials can be used in low thickness.…”
Section: Discussionsupporting
confidence: 84%
“…The described minimally invasive approaches include the following: (a) direct techniques with light‐cured composites, which constitute the most commonly reported treatments; (b) indirect techniques with ceramic or composite partial bonded restorations; and (c) a combination of these two techniques 6 . Among the indirect techniques, a novel technique (one step‐no prep) for full‐mouth rehabilitation of worn dentition using computer‐aided designed and manufactured (CAD‐CAM) composite restorations has been recently introduced 7 . It is characterized by the absence of tooth tissue preparation (no prep) and provisional phase (one step), use of polymer‐infiltrated ceramic network (PICN) materials, occlusal analysis, and collaboration with physiotherapists to treat bruxism‐associated symptoms, such as muscular pain.…”
Section: Introductionmentioning
confidence: 99%
“…The interest of the CAD/CAM with the same procedure has already been shown in extensive erosive lesions [ 20 , 21 ] and traumatology [ 22 ]. For this patient, an improvement in masticatory performance is clearly visible.…”
Section: Discussionmentioning
confidence: 99%
“…14 Restoring functional occlusal relationships with the reconstruction of OVD requires a complex, multistep treatment. 15 The increase in OVD can be provided by one-or twostep approaches. The one-step approach employs a treatment modality that the definitive indirect restorations being all bonded within the same or following day, whereas provisional restorations or nightguards are applied to test the new OVD with the two-step approach.…”
Section: Discussionmentioning
confidence: 99%
“…12 Previous studies reported that an increase in OVD up to 5 mm in the maxillo-mandibular interincisal distance is well tolerated by patients and that one-step approach is applicable. 15,16 On the other hand, OVD increase in patients with severe attrition induces signs of neuroplastic changes in corticomotor control of masseter muscles. 17 Therefore, when alteration in OVD is planned for patients with TMD, two-step approach is suggested regardless of the amount of increase.…”
Section: Discussionmentioning
confidence: 99%